2017
DOI: 10.17216/limnofish.304140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Feed and Stocking Density on Survival and Growth Performance of Astacus leptodactylus (Esch., 1823) Juveniles

Abstract: The aim of this study was to investigate the combined effects of two stocking densities (650 and 1300 juveniles/m 2) and diets (live feed-Daphnia magna and commercial trout feed) on survival rate and growth performance of Astacus leptodactylus juveniles. Juveniles in the second developmental stage were used in the experiment. Final survival rate and growth paremeters of juveniles were evaluated at the end of experiment (90 days). The results of this study indicated that diets were not found effective on surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…The use of H. illucens meal in the diet significantly affected the survival, growth performance and feed utilization of P. leptodactylus. It is worth mentioning that the survival rates observed in this study were similar (Ulikowski et al, 2006;Erol et al, 2017) or lower with those reported in other studies with the species (Mazlum et al, 2011;Hu et al, 2019). Certainly, the fact that P. leptodactylus is not yet a conventional farmed crustacean species, with rearing protocols and nutrient balanced diets still being investigated, may partly explain the low survival rates observed in the present study.…”
Section: Growth Performance and Feed Utilizationsupporting
confidence: 88%
“…The use of H. illucens meal in the diet significantly affected the survival, growth performance and feed utilization of P. leptodactylus. It is worth mentioning that the survival rates observed in this study were similar (Ulikowski et al, 2006;Erol et al, 2017) or lower with those reported in other studies with the species (Mazlum et al, 2011;Hu et al, 2019). Certainly, the fact that P. leptodactylus is not yet a conventional farmed crustacean species, with rearing protocols and nutrient balanced diets still being investigated, may partly explain the low survival rates observed in the present study.…”
Section: Growth Performance and Feed Utilizationsupporting
confidence: 88%
“…These results clearly show that there may be important ingredients in the structure of the formulated feed, apart from the protein ratio. For instance, Erol et al (2017) fed the 2.5 cm narrow-clawed crayfish (Astacus leptodactylus) with a 55% protein ratio of trout feed and the authors recorded the highest total and carapace lengths in this group. But we found the highest FMTL and FMCL in the red swamp crayfish fed with crustacean feed among the S1 groups.…”
Section: Discussionmentioning
confidence: 99%